2019
DOI: 10.1111/petr.13473
|View full text |Cite
|
Sign up to set email alerts
|

The difficult abdominal closure after paediatric intestinal transplantation: Use of abdominal rectus muscle fascia and literature review

Abstract: Primary abdominal wall closure after intestinal and multivisceral transplantation may not be possible because of loss of abdominal domain and/or graft size/abdominal cavity mismatch. Traditional closure techniques for the open abdomen may not be valid in these circumstances because of severe scarring of the abdominal wall from multiple previous surgeries in this particular group of patients. We present our initial experience with the use of non‐vascularized abdominal rectus muscle fascia in two patients who un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 16 publications
(24 reference statements)
0
37
0
Order By: Relevance
“…The search resulted in a total of 59 abstracts, including 2 additional abstracts found in the second search [2,10]. Another 4 abstracts were identified through other sources [8,14,19,20], namely congress proceedings and reference scanning.…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The search resulted in a total of 59 abstracts, including 2 additional abstracts found in the second search [2,10]. Another 4 abstracts were identified through other sources [8,14,19,20], namely congress proceedings and reference scanning.…”
Section: Study Selectionmentioning
confidence: 99%
“…The final 9 full-text articles included 6 case series [1,3-5,14,15] and 3 case reports [2,10,24]. All of them were based on a retrospective study design, although 1 mentioned the use of prospectively collected data [3].…”
Section: Descriptive Analysis 2421 Study Type and Design All Included...mentioning
confidence: 99%
See 2 more Smart Citations
“…-Signed consent form from donor and recipient families tumors requiring abdominal wall resection, ischemia-reperfusion graft edema associated with compartment syndrome, and vascular complications leading to increased intra-abdominal pressure. 4,[8][9][10]12 It has been reported that 20-50% of patients who undergo IT will need an alternative technique to conventional primary closure of the abdominal wall. 6,13 However, these patients are generally in poor health, and, therefore, reconstructive surgery or the use of abdominal flaps is not recommended.…”
Section: Indications For Abdominal Wall Transplantationmentioning
confidence: 99%